Tuberculosis control in people living with HIV/AIDS - Gabriela Tavares Magnabosco; Lívia Maria Lopes; Rubia Laine de Paula Andrade; Maria Eugênia Firmino Brunello; Aline Aparecida Monroe; Tereza Cristina Scatena Villa
ABSTRACT Objective: to analyze the offering of health actions and services for the control of tuberculosis for people living with HIV/AIDS being followed up in the Specialized Care Services for HIV/AIDS in Ribeirão Preto, SP, Brazil. Method: quantitative, exploratory survey study. Participated 253 people living with HIV/AIDS followed up by this service, considering as inclusion criteria: individuals older than 18 years living in the city and not inmates. Data collection was conducted from January 2012 to May 2013 through interviews with the support of a specific instrument. Data were analyzed using indicators and a composite index. Results: the offering of services for the control of tuberculosis in people living with HIV/AIDS by municipal services was considered as intermediate, reinforcing the need for better planning for comprehensive assistance, coordination of professionals in teams and among the services network, in addition to professional training and continuing education. Conclusion: it is necessary to implement strategies that promote shared actions between TB and HIV / AIDS programs and between different services in order to strengthen the local care network, aimed at producing an individualized care, comprehensive and responsive.